Demand for Piped and Non-piped Water Supply Services : Evidence from Southwest Sri Lanka - Nauges, Celine (2012)
In many countries, water supply is a service that is seriously underpriced, especially for residential consumers. This has led to a call for setting cost recovery policies to ensure that the tariffs charged for water supply cover the full cost of service provision. Identification of factors driving piped and non-piped water demand is a necessary prerequisite for predicting how consumers will react to such price increases. Using cross-sectional data of 1,800 households from Southwest Sri Lanka, we estimate water demand functions for piped and non-piped households using appropriate econometric techniques. The (marginal) price elasticity is estimated at -0.15 for households exclusively relying on piped water, and at -0.37 for households using piped water but supplementing their supply with other water sources. The time cost elasticity for households relying on non-piped water only is estimated at -0.06 on average, but varying across sources. For both piped and non-piped households, we find evidence of substitutability between water from different sources. We discuss the implications of these results in terms of pricing policy.